2021
DOI: 10.1111/jcmm.16852
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NCBP3 on METTL3‐mediated m6A RNA methylation to enhance translation process in hypoxic cardiomyocytes

Abstract: Hypoxia as a crucial pathogenesis factor usually results in huge harmful effects on cardiac injury and dysfunction. Our previous study has uncovered the global transcriptome and translatome profiles of cardiomyocytes in vitro and in vivo to response to hypoxia by RNA sequencing and ribosome profiling sequencing. We observe a series of differential expressed genes between transcription and translation, which may be attributed to the hypoxia‐specific binding affinity of nuclear cap‐binding subunit 3 (NCBP3) at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Hypoxia-inducible m 6 A deposition by METTL3 was recently described to operate specifically in cardiomyocytes, which could possibly provide an operating rationale for some of the above speculations. 144 Namely, a hypoxia-inducible, cardiomyocyte-enriched, and mesoderm-restricted upregulation of a nuclear cap-binding subunit 3 (NCBP3) protein was identified to occupy the 5′ UTRs of 85 distinct mRNAs in hypoxic cardiomyocytes with a striking 87.6% congruency to a previously published hypoxic cardiomyocyte dataset of transcripts with incongruent translation activity to their transcriptomic expression. 346 NCBP3 was shown to recruit METTL3, promoting the bound mRNA m 6 A methylation and eukaryotic translation initiation factor 4A2 (eIF4A2) to initiate their translation.…”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 90%
See 2 more Smart Citations
“…Hypoxia-inducible m 6 A deposition by METTL3 was recently described to operate specifically in cardiomyocytes, which could possibly provide an operating rationale for some of the above speculations. 144 Namely, a hypoxia-inducible, cardiomyocyte-enriched, and mesoderm-restricted upregulation of a nuclear cap-binding subunit 3 (NCBP3) protein was identified to occupy the 5′ UTRs of 85 distinct mRNAs in hypoxic cardiomyocytes with a striking 87.6% congruency to a previously published hypoxic cardiomyocyte dataset of transcripts with incongruent translation activity to their transcriptomic expression. 346 NCBP3 was shown to recruit METTL3, promoting the bound mRNA m 6 A methylation and eukaryotic translation initiation factor 4A2 (eIF4A2) to initiate their translation.…”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 90%
“… 346 NCBP3 was shown to recruit METTL3, promoting the bound mRNA m 6 A methylation and eukaryotic translation initiation factor 4A2 (eIF4A2) to initiate their translation. 144 …”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid gene expression after hypoxia stress is required to prevent cardiomyocytes from the hypoxia-induced injury. As the most abundant RNA modification, m6A methylation is dramatically up-regulated in cardiomyocytes after hypoxia exposure ( Fry et al, 2017 ; Chokkalla et al, 2019 ; Ye et al, 2021 ). Ye et al reported that m6A methylation at the 5′-UTR of hypoxia-related mRNA is upregulated via overexpression of METTL3 induced by hypoxia; and this promote the localization of eIF4A2 to target genes and enhance the translation of these genes in hypoxic cardiomyocytes, which can alleviate hypoxia-induced injury ( Ye et al, 2021 ; Table 3 and Figure 2 ).…”
Section: M6a Methylation and Cvdsmentioning
confidence: 99%
“…In addition to the YTH family, recent study found that the m6A writer can also interact with eIF4A2 to facilitate gene expression in cardiac cells under hypoxic conditions via the scaffold function of nuclear cap-binding subunit 3 (NCBP3) ( 31 ). Besides, the METTL3 was also found to be involved in the RNA splicing process.…”
Section: Biological Function Of M6amentioning
confidence: 99%